Neuroimaging study of electroconvulsive therapy for depression - Xiaolu Chen; Hanjie Yang; Long-Biao Cui; Long-Biao Cui; Xiao Li (Frontiers in Psychiatry, 2023)
Electroconvulsive therapy (ECT) is an important treatment for depression. Although it is known as the most effective acute treatment for severe mood disorders, its therapeutic mechanism is still unclear. With the rapid development of neuroimaging technology, various neuroimaging techniques have been available to explore the alterations of the brain by ECT, such as structural magnetic resonance imaging, functional magnetic resonance imaging, magnetic resonance spectroscopy, positron emission tomography, single photon emission computed tomography, arterial spin labeling, etc. This article reviews studies in neuroimaging on ECT for depression. These findings suggest that the neurobiological mechanism of ECT may regulate the brain functional activity, and neural structural plasticity, as well as balance the brain’s neurotransmitters, which finally achieves a therapeutic effect.